Cartographic Mexico : a history of state fixations and fugitive landscapes - Craib, Raymond B. (Latin America otherwise., 2004)
'Cartographic Mexico' analyses the spatial history of 19th & early 20th century Mexico, particularly the political uses of mapping & surveying, in order to demonstrate the multiple ways that space can be negotiated in the service of local or national agendas.